2004
DOI: 10.1111/j.1075-122x.2004.21323.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Following Breast-Conserving Therapy or Mastectomy: Results of a 5-Year Prospective Study

Abstract: There are many conflicting results in the literature comparing quality of life following breast-conserving therapy (BCT) and mastectomy. This study compared long-term quality of life between breast cancer patients treated by BCT or mastectomy in three age groups. Patients (n = 990) completed a quality of life survey, including the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30), at regular intervals over 5 years. In the cross-sectional data, mastect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
212
4
42

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(286 citation statements)
references
References 36 publications
19
212
4
42
Order By: Relevance
“…Engle et al (2004) in their study, found that many patients assume they would experience a situation like organ removal after mastectomy. For this reason, they often look for treatments other than mastectomy not to lose the organ which is sign of being female and mother for them (Engle et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Engle et al (2004) in their study, found that many patients assume they would experience a situation like organ removal after mastectomy. For this reason, they often look for treatments other than mastectomy not to lose the organ which is sign of being female and mother for them (Engle et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Mastectomy patients had significantly (p<0.01) lower body image, role and sexual functioning scores, and their lives were overall more disrupted than breast-conserving therapy patients [40]. Importantly, body image, sexual functioning and lifestyle disruptions did not improve over time [40].…”
Section: Pharmacologic Effectsmentioning
confidence: 94%
“…Importantly, body image, sexual functioning and lifestyle disruptions did not improve over time [40]. Breast conserving therapy, when oncologically appropriate, should be encouraged in all age groups.…”
Section: Pharmacologic Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Uma decisão favorável para essa modalidade de tratamento -a lumpectomia -pode ter repercussão imediata na saúde mental da mulher pela questão da "imagem corporal", um termo que, segundo Engel et al (2004), é falho em descrever a complexidade da experiência psicossocial em perder uma mama.…”
Section: O Diagnóstico De Transtornos Mentais Em Mulheres Com Câncerunclassified